TEORI KONSUMSI ISLAMI: STRATEGI MEWUJUDKAN MASLAHAH - Muhammad Irawan; Ichsan Iqbal (Tijarah: Jurnal Ekonomi Syariah, 2026)
Consumption in Islamic economics is not merely an activity to fulfill material needs but also encompasses spiritual and social dimensions aimed at achieving maslahah (public benefit and welfare). This study examines the concept of Islamic consumption, the hierarchy of human needs, consumption ethics, and the role of maslahah in promoting well-being. The research employs a qualitative approach through library research and content analysis of Islamic economic literature. The findings reveal that Islamic consumption is guided by a hierarchy of needs consisting of dharuriyyah (essential needs), hajiyyah (complementary needs), and tahsiniyyah (refinement needs), as well as the principles of tawhid, justice, trustworthiness, permissibility (halal), and moderation. Maslahah serves as the primary objective of consumption by safeguarding the five essential elements of maqashid al-shari’ah: religion, life, intellect, lineage, and wealth. Therefore, Islamic consumption extends beyond individual satisfaction to the realization of social welfare and sustainable prosperity in both this world and the hereafter. This study contributes to the literature by offering a novel integrative synthesis of classical maslahah theory and modern consumption ethics to establish operational boundaries for contemporary Muslim consumer behavior. ABSTRAKKonsumsi dalam ekonomi Islam merupakan aktivitas yang tidak hanya bertujuan memenuhi kebutuhan materi, tetapi juga mengandung dimensi spiritual dan sosial untuk mencapai maslahah. Penelitian ini bertujuan mengkaji konsep konsumsi Islami, hierarki kebutuhan manusia, etika konsumsi, serta peran maslahah dalam mewujudkan kesejahteraan. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi pustaka (library research) dan analisis isi (content analysis). Hasil kajian menunjukkan bahwa konsumsi Islami berlandaskan hierarki kebutuhan dharuriyyah, hajiyyah, dan tahsiniyyah, serta prinsip tauhid, keadilan, amanah, kehalalan, dan kesederhanaan. Konsep maslahah menjadi tujuan utama konsumsi karena berorientasi pada perlindungan agama, jiwa, akal, keturunan, dan harta (maqashid al-syari’ah). Dengan demikian, konsumsi dalam Islam tidak hanya berfokus pada kepuasan individu, tetapi juga pada terciptanya kesejahteraan sosial dan kebahagiaan dunia-akhirat. Kajian ini memberikan kontribusi kebaruan melalui sintesis kritis integratif antara teori maslahah klasik dengan instrumen etika konsumsi guna merumuskan batasan operasional perilaku konsumen Muslim.